What Really Drives Public Debt : A Holistic Approach - Anaya, Pablo (IMF Working Papers; Working Paper ;, 2015)
This paper presents a novel approach to detail the propagation of shocks to public debt. The modeling technique involves a structural vector auto-regression (SVAR) estimator with an endogenous debt accumulation equation. It explores how the main drivers of sovereign debt dynamics-the primary balance, the interest rate, growth and inflation-interact with each other. Such analysis is particularly useful for debt sustainability analysis. We find that some interactions exacerbate the impact of shocks to the accumulation of debt, while others act to stabilize debt dynamics. Furthermore, the choice of monetary policy regime plays an important role in these debt dynamics - countries with constrained monetary policy are more at risk from changes in market sentiment and must rely much more on fiscal policy to constrain debt.